Corporate Governance and Tax Management - Rizqy Aiddha Yuniawati (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to examine the effect of corporate governance on tax management which is proxied by a cash effective tax rate. The corporate governance mechanisms used are institutional ownership, audit committees, independent commissioners, and external auditors. The population in this study is manufacturing companies listed on the Stock Exchange after the imposition of a flat tax rate of 25%, in period 2015 to 2018. This study uses purposive sampling criteria so that the samples obtained are 48 companies. The type of data used in this study is secondary data. The data analysis technique in this study uses multiple linear regression analysis. The results of this study indicate that institutional ownership has a significant positive effect on tax management; the audit committee has no significant negative effect on tax management; independent commissioners have insignificant negative effect on tax management, and external auditors have significant positive effect on tax management